Getting to Know PPnBM: Sales Tax on Luxury Goods and the Impact on the Automotive Industry, Indonesia - Mira Agustia; Siti Zahara; Olivia Deslovita Br, Ginting; Kartika Sari; Karnisa Maharani; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the impact of Luxury Goods Sales Tax (PPnBM) on the automotive industry in Indonesia. This study uses a literature study method by analyzing data from literature sources. The results of the study indicate that PPnBM has positive and negative impacts on the automotive industry. The positive impacts are increasing state revenue, regulating income distribution, encouraging the local automotive industry, and increasing public awareness of the importance of paying taxes. However, the negative impacts are affecting employment in the automotive industry and increasing unemployment.